Global extent and change in human modification of terrestrial ecosystems from 1990 to 2022 - David M. Theobald; James R. Oakleaf; Glenn Moncrieff; Maria Voigt; Joe Kiesecker; Christina M. Kennedy (Scientific Data)
Abstract Habitat loss and degradation associated with industrial development is the primary threat and dominant driver of biodiversity loss globally. Spatially-explicit datasets that estimate human pressures are essential to understand the extent and rate of anthropogenic impacts on ecosystems and are critical to inform conservation commitments and efforts under the Global Biodiversity Framework. We leveraged the human modification framework to generate comprehensive, consistent, detailed, robust, temporal, and contemporary datasets to map cumulative and individual threats associated with industrial human activities to terrestrial biodiversity and ecosystems from 1990 to 2022. In ~2022, 43% of terrestrial lands had very low levels of modification, while 27%, 20%, and 10% had low, moderate, and high modification, respectively. Nearly 2/3 of biomes and 1/2 of ecoregions currently are moderately-modified, and 24% of terrestrial ecosystems (31 M km2) experienced increased modification from 1990 to 2020. About 29% of countries and 31% of ecoregions might also be particularly vulnerable to biodiversity loss given their above-average increased modification and less than 30% protection.